Incidence of postoperative dyspepsia is not associated with prophylactic use of drugs - Tsuchie, Sara Yumi; Nani, Fernando Souza; Vieira, Joaquim Edson (São Paulo Medical Journal, 2014)
CONTEXT AND OBJECTIVE: Preoperative fasting guidelines do not recommend H2 receptor antagonists or proton pump inhibitors. This study investigated prophylactic use of gastric protection and the incidence of dyspeptic symptoms in the immediate postoperative period. DESIGN AND SETTING: Non-randomized observational investigation in a post-anesthesia care unit. METHODS: American Society of Anesthesiologists risk classification ASAP1 and ASAP2 patients over 18 years of age were evaluated to identify dyspeptic symptoms during post-anesthesia care for up to 48 hours, after receiving or not receiving prophylactic gastric protection during anesthesia. History of dyspeptic symptoms and previous use of such medications were exclusion criteria. The odds ratio for incidence of dyspeptic symptoms with use of these medications was obtained. RESULTS: This investigation studied 188 patients: 71% women; 50.5% ASAP1 patients. Most patients received general anesthesia (68%). Gastric protection was widely used (n = 164; 87.2%), comprising omeprazole (n = 126; 76.8%) or ranitidine (n = 38; 23.2%). Only a few patients did not receive any prophylaxis (n = 24; 12.8%). During the observation, 24 patients (12.8%) reported some dyspeptic symptoms but without any relationship with prophylaxis (relative risk, RR = 0.56; 95% confidence interval, CI: 0.23-1.35; P = 0.17; number needed to treat, NNT = 11). Omeprazole, compared with ranitidine, did not reduce the chance of having symptoms (RR = 0.65; 95% CI: 0.27-1.60; P = 0.26; NNT = 19). CONCLUSION: This study suggests that prophylactic use of proton pump inhibitors or H2 receptor antagonists was routine for asymptomatic patients and was not associated with postoperative protection against dyspeptic symptoms.